Confronting long-term unemployment through social entrepreneurship : an action research study - Nolan, Patrick (Trinity College (Dublin, Ireland). Trinity Business School, 2004)
This thesis emerges from the action-learning M.Sc which was completed at Trinity College, Dublin six years ago (Nolan, 1997). Through that thesis, and the associated learning processes of the programme, a concept was developed for the creation and structure of an organisation using the practice of social entrepreneurship to confront long-term unemployment in Dublin. Following a year of further examination, reflection and work, that project was launched by the Taoiseach, Mr. Bertie Ahern TD, in March 1999. The project has been successful in training and placing in employment many previously long-term unemployed persons from disadvantaged communities in the Dublin region.
Keywords: Business Studies, Ph.D.; Ph.D. Trinity College Dublin